Synthesis and evaluation of hydrogen peroxide sensitive tofacitinib prodrugs - Viola Previtali; Ulrik Bering Keiding; Asger Hegelund Olsen; Jorge Peiró Cadahía; Anne Skovsbo Clausen; Andreas Kjaer; Thomas Lars Andresen; Anders Elias Hansen; Mads Hartvig Clausen (Elsevier, 2022)
Tofacitinib (CP-690,550), an approved Janus kinase (JAK) inhibitor, has been proven highly efficacious in treating rheumatoid arthritis (RA). Unfortunately, tofacitinib's clinical application has been limited by adverse side effects that arise from its pan-JAKs inhibition and ubiquitous biodistribution. In this study, we have examined whether a reactive oxygen species (ROS)-activated prodrug design could be applied to tofacitinib to potentially avoid its systemic JAK inhibition and thereby reduce its adverse effects. The prodrug strategy selected is based on ROS-labile 4-methylphenylboronic acid pro-moieties linked to the drugs via a carbamate linkage (prodrug 1) or a direct C-N bond (prodrug 2). Activation under pathophysiological concentrations of H2O2 was investigated and conversion to desired tofacitinib assessed. The most promising prodrug candidate, prodrug 2, was selected in agreement with relevant in vitro physicochemical assay and in silico predicted ADME properties. Selected candidate prodrug 2 showed a remarkable potency window compared to tofacitinib in an in vitro kinase assay against JAK1 and JAK3 kinases. Importantly, prodrug 2 displayed a similar pharmacokinetic profile to tofacitinib after single dose i.p. administration to DBA/1 mice. This study supports the promising applications of ROS-sensitive tofacitinib prodrugs. Their further development and applicability would enhance tofacitinib's therapeutic efficacy, and may provide an opportunity for future development of safer tofacitinib dosing regimens.